Checklist of grasshoppers (Orthoptera: Acridoidea) from Reserva Florestal Adolpho Ducke, State of Amazonas, Brazil, and New Records for the Country - Da Costa, Maria Kátia Matiotti; Luciano De, P. Martins; Zefa, Edison; Redü, Darlan Rutz; Morselli, João Paulo; De Assis G. De Mello, Francisco [UNESP] (Pensoft Publishers, 2015)
We present a list of grasshoppers from the Reserva Florestal Adolpho Ducke, a preservation area in the outskirts of Manaus, State of Amazonas, Brazil. The Ducke Reserve has been an indispensable tool for scientific development due to its considerable floristic richness. It has provided ample material for studies and research, promoting the conservation of Amazonian rainforest flora and fauna and the protection of endangered species. This checklist is intended to provide basic information on the regional grasshopper fauna, expand the current knowledge of species occurrences, and serve as a basis for systematists interested in revisionary and biogeographic work with a focus on Amazonian endemic areas. We sampled the Ducke Reserve for fifteen days using active and visual searching methods. We collected 38 species of terrestrial and semi-aquatic grasshoppers, 23 which belonged to the Acrididae and 15 to Romaleidae. Twenty four species and subspecies of grasshopper were registered for the first time for the locality and three new species and one new subspecies were recorded for Brazil.
Keywords: geographical distribution; Manaus; species; species richness; taxonomy